A 75‐year pictorial history of the Cayo Santiago rhesus monkey colony. Issue 1 (12th March 2015) - Kessler, Matthew J.; Rawlins, Richard G.
Abstract : This article presents a pictorial history of the free‐ranging colony of rhesus monkeys ( Macaca mulatta ) on Cayo Santiago, Puerto Rico, in commemoration of the 75th anniversary of its establishment by Clarence R. Carpenter in December 1938. It is based on a presentation made by the authors at the symposium, Cayo Santiago: 75 Years of Leadership in Translational Research, held at the 36th Annual Meeting of the American Society of Primatologists in San Juan, Puerto Rico, on 20 June 2013. Am. J. Primatol. 78:6–43, 2016. © 2016 Wiley Periodicals, Inc.